Why is pancreatic cancer so deadly? The pathologist's view. Issue 2 (15th April 2019) - Hruban, Ralph H; Gaida, Matthias M; Thompson, Elizabeth; Hong, Seung‐Mo; Noë, Michaël; Brosens, Lodewijk AA; Jongepier, Martine; Offerhaus, G Johan A; Wood, Laura D
Abstract: The remarkable aggressiveness of pancreatic cancer has never been fully explained. Although clearly multifactorial, we postulate that venous invasion, a finding seen in most pancreatic cancers but not in most cancers of other organs, may be a significant, underappreciated contributor to the aggressiveness of this disease. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.